Gender Quotas and Women's Political Leadership - Diana Z. O'Brien; Johanna Rickne (Research Institute of Industrial Economics (IFN), 2014)
Though more than 100 countries have adopted gender quotas, the impacts of these reforms on women's political leadership remain largely unknown. We exploit a quasi-experiment - a zipper quota imposed by the Swedish Social Democratic national party on municipal party groups - to examine quotas' effect on women's selection and survival as leaders within their parties. We find that those municipalities where the quota had a larger impact became more likely to appoint female leaders, but not more likely to support the reelection of women to the post. Extending this analysis, we show that the quota increased the number of qualified female candidates without increasing the diversity among women within the group. These results lend support to the notion that quotas may have an acceleration effect on women's representation in leadership posts and help dispel the myth that quotas trade short-term gains in women's descriptive representation for long-term exclusion from political power.
Keywords: G34; G38; J20; J48; 330; Gender quotas; Political leadership; Party leaders; Political careers; Electoral reforms; Women and politics; Subnational politics